2020
DOI: 10.2196/18581
|View full text |Cite
|
Sign up to set email alerts
|

Googling for Ticks and Borreliosis in Germany: Nationwide Google Search Analysis From 2015 to 2018

Abstract: Background Borreliosis is the most frequently transmitted tick-borne disease in Europe. It is difficult to estimate the incidence of tick bites and associated diseases in the German population due to the lack of an obligation to register across all 16 federal states of Germany. Objective The aim of this study is to show that Google data can be used to generate general trends of infectious diseases on the basis of borreliosis and tick bites. In addition,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 25 publications
(24 reference statements)
3
17
1
11
Order By: Relevance
“…Google Trends has been shown to be suitable for studying seasonal patterns of various skin problems. 47 , 48 , 49 , 50 In line with previous studies, we found a seasonal pattern for the internet interest for ticks with peaks of interest in May. 49 , 50 Expectedly, there was a peak of interest for insect stings in July.…”
Section: Discussionsupporting
confidence: 91%
“…Google Trends has been shown to be suitable for studying seasonal patterns of various skin problems. 47 , 48 , 49 , 50 In line with previous studies, we found a seasonal pattern for the internet interest for ticks with peaks of interest in May. 49 , 50 Expectedly, there was a peak of interest for insect stings in July.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, the majority of cities had their largest search volume in October 2015, which was mainly caused by an increase of searches for chlamydia-related keywords, and which indicates a national rather than regional trend. In contrast to studies that investigated pruritus, skin cancer, or borreliosis, no seasonal variations were detected [ 28 , 32 , 33 ], which suggests that interest in STIs is independent of periodic external factors such as climate. The few observed national peaks in search volume may be due to increased media coverage, as seen in other studies [ 40 , 41 ].…”
Section: Discussioncontrasting
confidence: 70%
“…In general, the internet is frequently used as a source for health-related information [ 16 , 52 ], and search engine data have been successfully used in prior studies to describe population interests and behavior with regard to public health topics [ 27 , 28 , 53 , 54 ]. The advantage is the great amount of data, which can be easily and anonymously acquired from millions of people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pet owners are concerned about ectoparasites and vector-borne pathogens with ever-increasing online searching for relevant information [6,21]. Yearly, pet owners purchase 5.2 billion US dollars in ectoparasiticidal products to protect their pets from these pests [22].…”
Section: Introductionmentioning
confidence: 99%